A Survival Guide for Research Scientists - Tantra, Ratna (Springer International Publishing : Imprint: Springer, 2019)
The ultimate companion book that will look after you and your research career Research scientists play a pivotal role in society. Their passion for science will drive them forward, leading to new discoveries that will ultimately make the world a better place. Unfortunately, as the professional environment becomes more and more competitive, research scientists today cannot just rely on technical knowledge to carve successful careers. Besides technical skills, they will need to acquire other skills, such as how to communicate their science to the outside world. A Survival Guide for Research Scientists is a one-stop-shop that will help you to develop those core skills not often taught at school or university. The book has been written by an author with more than 20 years of scientific research experience (across different scientific disciplines). She has not only been a research scientist but also a writer, a consultant, a sole-trader and aproject manager. A Survival Guide for Research Scientists takes on a holistic approach in order to help you pave the way for success. As such, it features practical guidelines on how to: • conduct your scientific research (how to: do literature review, design experiments, adopt best practice, ensure health and safety, etc.). • write and edit (reports, bid proposals, peer review publications, etc). • interact with the outside world (be a team leader, manage a project, network, deal with difficult people, do presentations, organise meetings, etc.). • look after your career (and get your dream job). • look after yourself (and how to manage stress). • look for a job (develop your CV, prepare for interviews, etc.). • become self-employed (and achieve business success). • deal with redundancy (and move forward in life, etc). Whatever your scientific background may be, this book is theperfect accompaniment, to guide you at every stage of your career.